232 Impact of clinical guidelines in France. (23rd September 2015) - Vendittelli, F; Rivière, O; Crenn-Hébert, C
Abstract : Context and Objectives: Clinical practice guidelines (CPGs) covering the perinatal period are published regularly by French College of Gynaecologists and Obstetricians as well as by the National Authority for Health. Nonetheless, assessment of the impact of these guidelines is not routinely considered in France. The objective of this work is to describe the trends in practices before and after CPGs are issued in France. Programme: Between 1994 and 2005, Audipog received data from 209 public and private maternity units for a database covering 247 807 pregnancies. We constructed a random subsample for each year by including only the births occurring during a single month for each maternity ward. Our study analyzes therefore 103 141 pregnancies and 104 454 births. Because of the voluntary nature of participation in Audipog, its distribution of maternity units according to legal status and region differed from that of France as a whole, a difference that must be taken into account in the analysis. Eight sets of national CPGs were analysed in this study. Results: The 1998 CPG had little impact, for the rate of infants weighing <1500 g born in Level III units has remained stable since 1998, at around 70%. The rate of babies born before 33 weeks of gestation in a Level III facility in 2005 has returned to the rate in 1994 (53%). The caesarean rate in nulliparas has remained stable, at around 20% (RPC2000). The rate of antenatal corticosteroid therapy among the births before 33 weeks rose from 42% to 50% between 2000 and 2005 (RPC 2002). Breast-feeding at discharge has been rising slowly (51% in 2000 and 58% in 2005)(RPC 2002). Smoking among pregnant women has been falling continually but slowly since 1994 (RPC 2003). Active management of the third stage of labour rose from 1994 (6%) to 2004 (30%) but remained at 31% in 2005 (RPC 2004). Early discharge after delivery has increased since 1994, independently of the CPG in 2004. The episiotomy rate has been dropping slowly since 1994 (55% in 1994 and 40% in 2005)(RPC 2005). Discussion and Conclusion: Practices were modified very little by CPGs, except for those concerning antenatal corticosteroid therapy, but practices often changed before the issuance of the guidelines. Research to determine how to optimise the dissemination of CPGs would be desirable. Contextes, objectifs: Des recommandations de pratiques cliniques (RPC) sont régulièrement publiées par le Collège des Gynécologues Obstétriciens Français ainsi que par la Haute Autorité de Santé en périnatalité. Pour autant, l'étude de l'impact de ces recommandations n'est pas systématiquement envisagé, en France. L'objectif de ce travail est de décrire l'évolution des pratiques avant et/ou après la mise en place de RPC, en France. Porgramme: L'Audipog a reçu, entre 1994-2005, des données de 209 maternités publiques ou privées, conduisant à un fichier de 247807 grossesses. Nous avons constitué pour chaque année, un sous échantillon, par tirage au sort, ne comprenant que 1es naissances survenues pendant un mois par maternité. Notre étude porte donc sur 103141 grossesses et sur 104454 naissances. La participation au Réseau étant volontaire, la distribution des maternités selon leur statut juridique et leur région diffère de celle de la France entière, ce qui nécessite d'en tenir compte dans l'analyse. 8 RPC nationales ont été retenues pour l'étude. Résultats: La RPC de 1998, a eu peu d'impact puisque le taux des <1500g naissant en niveau III stagne depuis 1998 vers 70%. Le taux des <33SA naissant en niveau III a rejoint celui de 1994 (53%). Le taux de césariennes chez la primipare est resté stable autour de 20% [RPC2000]. Le taux de corticothérapie anténatale parmi les naissances < 33SA est passé de 42% à 50% entre 2000-2005 [RPC2002]. L'allaitement maternel à la sortie de la maternité est en augmentation lente (51% en 2000 et 58% en 2005)[RPC2002). La consommation de tabac a diminué de façon continue mais lente depuis 1994 [RPC2003]. La délivrance dirigée a augmenté de 1994 (6%) à 2004 (30%) mais est resté à 31% en 2005 [RPC2004]. Les sorties précoces du post-partum augmentent depuis 1994 indépendamment de la RPC de 2004. Le taux d'épisiotomies diminue lentement depuis 1994 (55% en 1994 et 40% en 2005)[RPC2005]. Discussion, conclusion: Les pratiques ont été peu modifiées par les RPC, en dehors de celle portant sur la corticothérapie anténatale, mais elles se modifient souvent avant celles-ci. Des recherches pour chercher à optimiser la diffusion des RPC sont souhaitables.